INTEGRASI REMEDIASI MISKONSEPSI DALAM PEMBELAJARAN FLUIDA DINAMIS MENGGUNAKAN PENDEKATAN KONSEPTUAL INTERAKTIF DI SMA - Kurnia Sari; Tomo Djudin; Erwina Oktavianty (Universitas Tanjungpura, 2018)
AbstractThe aims of this research was determined the effect of integrated remediation misconception in fluid dynamics learning use interactive conceptual instruction to decreasing the number of student misconception in grade XI SMA Negeri 7 Pontianak. The research used pre-experimental design with one group pretest-posttest design involving 35 students of class XI IPA 2 as a sample which selected by intact group. Diagnostic test which consist osf 18 multiple choice question with open reasoning was used as research instrument to asses the number of students misconception. Based on the result, the everage percentage decrease of misconception students for each students equal to 71,14%. Based on an analysis using price obtained McNemar test, (348,82) > indicate the conception significant changes between before and after integrated remediation misconception in fluid dynamics learning use interactive conceptual instruction. The effectiveness of integrated remediation misconception in fluid dynamics learning use interactive conceptual instruction of DQM (The Decreasing of Quantity of the student that Misconception) equal to 71,46% in high category. Keywords: integrated remediation, misconception, interactive conceptual instruction, fluid dynamic